Sex, drugs and pupusas: Disentangling relationships in Echiteae (Apocynaceae) - Morales, J. F.; Endress, M. E.; Liede-Schumann, S.
Echiteae (Apocynaceae)comprises about 200 species divided among 19 genera, 16 of which are restricted to the Neotropics, the other 3 to the Paleotropics. There are two large genera, Prestonia and Parsonsia, in the Neotropics and Paleotropics, respectively, whereas three-fourths of the genera contain only one to four species. In this study DNA of 82 species was extracted and amplified for four molecular markers: three plastid (trnL intron+trnL-trnF intergenic spacer, rpl16 intron, matK + 5?/ 3? trnK intron)and the nuclear ribosomal region ITS. The ingroup comprised 70 species from 17 genera in the tribe, and included representatives of all subtribes; the outgroup included 5 species each from the two putatively most closely related tribes, Odontadenieae and Mesechiteae, as well as 2 rooting species. Phylogenetic analyses were conducted using Bayesian inference and maximum likelihood approaches. Echiteae and four of its subtribes (Echitinae, Parsonsiinae, Peltastinae, Prestoniinae)as currently circumscribed were shown to be non-monophyletic. The fifth subtribe, Pentalinoninae, though monophyletic, does not belong to Echiteae; it was resolved as sister to a clade of Odontadenieae, where it fits better, since in both the characteristic secondary compounds are cardenolides. Prestonia and Temnadenia were resolved as polyphyletic, with P. riedelii grouped with Rhodocalyx and T. ornata nested within Prestonia. Fernaldia is nested within Echites and Peltastes is nested in Macropharynx. Fourteen genera are maintained. The new subtribe Laubertiinae is proposed, as are the combinations resulting from the merging of Fernaldia and Peltastes and the transfer of P. riedelii and T. ornata to Rhodocalyx and Prestonia, respectively. In the ancestors of Echiteae, we hypothesize that an evolutionary shift took place in which steroidal alkaloids and/or cardenolides, characteristic for apocynoids, were replaced by parsonsine-type pyrrolizidine alkaloids as the predominant defense compounds.
Keywords: APOCYNOIDS; MOLECULAR PHYLOGENY; PARSONSIA; PRESTONIA; PYRROLIZIDINE ALKALOIDS; SYSTEMATICS